Neonatal Listeria innocua sepsis - Arumugam, Senthil Kumar; Govindharaj, Kaviyarasan; Subramaniam, Arunachalam; Rangasamy, Ramalingam (International Journal of Contemporary Pediatrics, 2021)
Neonatal listeriosis is a potentially life-threatening infection, usually caused by Listeria monocytogenes. It has a high case fatality rate and can cause severe neurological sequelae among survivors. Early-onset listeriosis is caused by vertical transmission through transplacental route, inhalation of infected amniotic fluid or through ascending infection from the vaginal colonization. We report fatal neonatal listeriosis in a 5 day old female infant caused by L. innocua. L. innocua is considered as non-pathogen and only few cases were reported in an immunocompromised individual.